Analysis of the Development and Business Opportunities of Digital Business in Indonesia in the Last Five Years - Lukito Angga Prasakti; Eddy Soeryanto Soegoto; Rahma Wahdiniwaty; Adam Mukharil Bachtiar (Green Publisher Indonesia, 2026)
Indonesia's digital economy has shown rapid growth over the past five years. The e-Conomy SEA 2024 report noted that the gross merchandise value (GMV) of the digital economy increased from US27 billion in 2018 to US90 billion in 2024, with projections of reaching US200–360 billion by 2030. The largest contribution comes from the e-commerce sector, which reached US65 billion in 2024. Meanwhile, the adoption of digital payments and fintech is increasing rapidly; Bank Indonesia reported that electronic money transactions increased from 47.2 trillion rupiah in 2018 to 594.2 trillion rupiah in 2024. This article is designed to map trends, analyze opportunities, and link digital business developments in Indonesia to government policies, technological developments, consumer behavior, and the startup and MSME ecosystems. The research will employ a systematic literature review approach and secondary data analysis from government reports, scientific journals, and industry surveys. In addition to examining e-commerce and fintech, the study will also examine the edtech subsector—which is projected to have a market value of US3.23 billion in 2024 with a predicted annual growth of 11.79% through and healthtech, with transaction value projected to increase from US16 billion in 2023 to US34 billion in 2027. Challenges such as digital infrastructure inequality, talent shortages, data privacy and cybersecurity regulations, and funding gaps will also be part of the analysis. This research is expected to provide a comprehensive mapping and strategic recommendations for the government, business actors, and researchers to strengthen Indonesia's digital business ecosystem.